Operationalizing Hadith in Digital Ta’aruf: A Living Hadith Study of TikTok @taarufmenikah - Muzakki, Muhammad Asgar (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
This study examines the function of hadith in digital ta’aruf practices facilitated by the TikTok account @taarufmenikah. Using a living hadith approach, the research analyzes 36 TikTok posts containing hadith or Qur’anic references and is supported by interviews with practitioners of online and offline ta’aruf conducted through snowball sampling. The findings indicate that the cited texts originate from authoritative sources with acceptable levels of authenticity but are presented in simplified and decontextualized forms adapted to TikTok’s short-video format. In this context, hadith functions as normative legitimization, motivational encouragement, pragmatic guidance, and interpretive simplification, while its authority is shaped less by traditional religious figures and more by platform visibility and repetition, reflecting a form of algorithmic authority. The study concludes that digital ta’aruf reshapes the relationship between religious texts, authority, and user practices, illustrating a contemporary form of living hadith in social media spaces. Penelitian ini mengkaji fungsi hadis dalam praktik ta’aruf digital yang difasilitasi oleh akun TikTok @taarufmenikah. Dengan menggunakan pendekatan living hadis, penelitian ini menganalisis 36 unggahan TikTok yang memuat kutipan hadis atau ayat Al-Qur’an serta didukung oleh wawancara dengan praktisi ta’aruf daring dan luring yang dikumpulkan melalui teknik snowball sampling. Temuan penelitian menunjukkan bahwa teks-teks yang dikutip berasal dari sumber otoritatif dengan tingkat kesahihan yang dapat diterima, namun disajikan dalam bentuk yang disederhanakan dan terlepas dari konteks klasik agar sesuai dengan format video singkat TikTok. Dalam konteks ini, hadis berfungsi sebagai legitimasi normatif, penguatan motivasi, panduan pragmatis, dan penyederhanaan makna, sementara otoritasnya dibentuk tidak lagi oleh figur keagamaan tradisional, melainkan oleh visibilitas dan repetisi platform, yang mencerminkan bentuk algorithmic authority. Penelitian ini menyimpulkan bahwa praktik ta’aruf digital membentuk ulang relasi antara teks keagamaan, otoritas, dan praktik pengguna, serta merepresentasikan bentuk living hadis kontemporer di ruang media sosial.